Discourse on Legal Protection of Underage Child Labor in Indonesia (Universitas Negeri Semarang, 2022)
The young generation of a child has the right to the opportunity to grow and develop as widely as possible. However, not all children can make it happen, especially children who are hampered by the family economy. To be the backbone of the family, the phenomenon of underage child labor is a serious problem. In the elucidation of the Labor and Child Protection Law itself, there is protection and sanctions against child workers. Apart from the rules issued by the government, it has also ratified international conventions in enforcing the legal protection of children. In research using library material collection, the authors examine the legal protection of child labour. Continuing in this phenomenon, studies are related to the various causes of the rise of child labor in society. Seeing from this phenomenon, it can be found that the government itself has not been able to optimize its efforts to deal with the problems that occur.